A note on the spectrographic studies of Munroe Jets - Sampooran, Singh; Ray, A.K.; Sastri, M.L.N. (Defence Science Journal, 2013)
Spectra of Munroe Jets with different metals as liners were taken with a glass Constant Deviation Spectrograph and a quartz Intermediate Spectrograph. Preliminary studies indicate that the metal in the jet is partly in the vapour state and partly in the form of small fragments.